Geoheritage 3. Attracting Students to the Earth Sciences: An Example of Individual and Collective Outreach Efforts by Industry, Academia and Secondary Education - Bank, Charly; Jackson, Deryk; Hymers, Lesley (Geoscience Canada, 2009)
SUMMARY Too few Canadian high-school students are pursuing post-secondary studies and career opportunities in the earth sciences. Given Canada’s wealth of renewable and non-renewable resources and their importance to society, it is imperative that students become literate in the earth sciences, and that they are encouraged to pursue career opportunities in the many fields that constitute the earth sciences. To achieve these goals, a number of out-reach efforts by members of industry, academia and secondary education have been initiated. We outline here an example of our own collaboration in one such program directed not only at students, but also at primary and secondary teachers, university faculty, industry representatives and government officials. Our program has achieved significant results, and so will continue. Others interested in increasing the profile of the earth sciences are encouraged to explore such new out-reach approaches.